C2C value creation: social anxiety and retail environment - Braz Becker Larissa Carine; Pizzutti Cristiane (Emerald Publishing Limited, 2022)
Purpose: Most customers want to interact, whether on social networks or on company websites. This study examines the relationship between customer-to-customer (C2C) interaction and value, considering the roles of social anxiety and the retail environment.
Design/methodology/approach: This paper presents three written-scenario experimental studies, where C2C interaction and the retail environment are manipulated, and social anxiety levels are measured. The settings and the measures are changed across the experiments to increase the results’ validity.
Findings: A three-way interaction among C2C interaction, social anxiety and retail environment has impacts on experience value and other value-related variables (satisfaction and positive mood). In the offline retail environment, as social anxiety levels increase, the effects of C2C interaction on these variables become weaker. In the online retail environment, as social anxiety levels increase, these effects become stronger.
Research limitations/implications: This article contributes to the literature in three ways. First, it investigates the downside of positive C2C interactions when considering social anxiety and the retail environment where they occur. Second, this paper amplifies the literature about value by extending it to other consumers who can affect the service experience. Finally, this study explores online C2C interaction in a retail environment, an aspect that has been neglected in the research about online interactions.
Practical implications: This paper suggests strategies to manage C2C interaction for customers of varying levels of social anxiety in offline and online retail environments in order to maximise value for them.
Originality/value: This paper challenges the widespread idea that a positive C2C interaction always leads to value. By considering social anxiety and the retail environment in C2C literature, this paper explains why and when it is a false notion.